At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
f(x)
(2, 0) and (3, 2)
m = y - y1
x - x1
m = 2 - 0
3 - 2
m = 2
y - y1 = m(x - x1)
y - 0 = 2(x - 2)
y = 2x - 4
f(x) = 2x - 4
g(x)
(2/3, 0) and (1, 2)
m = y - y1
x - x1
m = 2 - 0
1 - 2/3
m = 6
y - y1 = m(x - x1)
y - 2 = 6(x - 1)
y = 6x - 4
g(x) = 6x - 4
since both equations are linear that means the graphs will be straight lines with y-intercept being -4 for both of the graphs.
if,
g(x) = f(k*x)
f(x) = 2x - 4
f(k*x) = 2k*x - 4
6x - 4 = 2k*x - 4
6x = 2kx
6 = 2k
k = 3.
I hope the answer is correct. All the best!
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.